Keeping law enforcement connected : information technology needs from state and local agencies - Gordon, John, 1956-; Wallace, Brett Andrew; Tremblay, Daniel; Hollywood, John (RAND, 2012)
The National Institute of Justice strives to assist criminal justice practitioners on behalf of the Department of Justice through the scientific research, development, and evaluation of technologies and methods. Given that there are nearly 18,000 state and local law enforcement agencies in the United States, this is a challenge of great complexity, breadth, and depth. Thus, it is crucial to be aware of agencies' technology needs, as well as how they might learn about promising technologies and applications. To this end, RAND researchers conducted interviews with an extensive sample group to determine criminal justice technology priorities at the state and local levels, as well as the means by which these agencies commonly receive information on technology and the effectiveness of outreach efforts by the National Law Enforcement and Corrections Technology Center. Interview results indicated a strong across-the-board desire for knowledge management systems and low-cost, easily maintained surveillance systems, and further indicated that the Center needs to expand its outreach efforts to professional associations.